Is it True that Oil Palm Plantations are the Main Driver of Indonesia’s Tropical Forest Deforestation? - Santosa, Yanto; Sunkar, Arzyana; Kwatrina, Rozza Tri (International Journal of Oil Palm, 2020)
The extent to which oil palm has contributed to deforestation of primary forests is still an intensive debate in public space. Even though the term deforestation and the results of the study and study are still "debatable" and have not been scientifically valid, they have had a very debilitating effect and detrimental to Indonesia’s position in global trade because it is considered responsible for the destruction of primary natural forests in the Southeast Asia region. Therefore, since 2015, research has been carried out on the origin of status, history of land use, land-cover and biodiversity in several oil palm plantations in 6 provinces (Riau, North Sumatra, South Sumatra, Central Kalimantan, West Kalimantan and West Sulawesi). The results of the search for the origins of the status of oil palm plantations (according to the RTRWP) show that 98.56% of the candidates for oil palm plantation areas are "not forested", namely: APL (54.93%), Plantation and Agriculture (42.19%). Furthermore, the results of interpretation of Landsat imagery on the condition of vegetation cover at 1 year before being made into oil palm plantations indicate that the type of land cover is no longer in the form of primary forest, but already in the form of shrubs and bare-land or rubber-plantation (68,91%). Likewise with the results of the search history of land use (see slide) where 71.29% of the land under study is the land of ex-community gardens, fields, transmigration land, or ex-HGU of other companies. While the rest (28.71%) is ex-HPH land. Referring to the juridical definition of "deforestation", this data shows that oil palm plantation land which is the location of the study "is not the result of deforestation". Referring to both the juridical definition and the FAO/World Bank definition of "deforestation", this data shows that oil palm plantation land which is the location of the study "is not a direct cause of primary deforestation".